Formulation, Design, and Optimization of Taste Masked Effervescent Tablet Containing Methocarbamol: Effervescent Tablet Containing Methocarbamol - Taymouri, Somayeh; Mostafavi, Abolfazl; Mahmoodi, Hamid (Iranian Journal of Pharmaceutical Sciences, 2021)
Methocarbamol is a skeletal muscle relaxant drug. In this study, we investigated the potential of developing methocarbamol effervescent tablets to facilitate drug administration. Effervescent tablets containing 1000 mg methocarbamol were prepared using the direct compression method. The effect of various formulations parameters such as citric acid, sodium bi-carbonate, PEG 6000, and PVP k30 on different physicochemical properties of tablets was evaluated at two levels. Different formulations with various amounts of mentioned excipients and the constant amount of methocarbamol, sucralose, mannitol, and different flavoring agents were prepared, and their properties included hardness, friability, pH effervescent time, CO2 content, and taste were studied. The optimized formulation was B8, which contained 400 mg of citric acid, 525 mg of sodium bicarbonate, 226.5 mg of PVP k30, 113.2 mg of PEG 6000, 100 mg of mannitol, and 30 mg of sucralose. This formulation had an effervescent time of 112.67± 2.05 seconds, hardness of 71.10± 2.51 N, and pH of 6.01±0.02. Statistical analysis by Design-Expert software showed that the hardness of tablets is mainly affected by the amount of PEG 6000. Volunteers reported that sour cherry had the most pleasant taste to them. In conclusion, current effervescent tablets are shown to be suitable vehicles for methocarbamol with potential for use in patients with swallowing problems and will enhance patient compliance.